Updated analysis of changes in locomotor activities across periods in an international ice hockey game - Franck Brocherie; Olivier Girard; Gregoire P. Millet (Termedia Publishing House, 2018)
The aim of this study was to examine changes in time-motion patterns of elite male ice hockey players during an international game with special reference to the development of fatigue. Ten elite male ice hockey players were filmed during an official international game. Detailed time-motion patterns and behaviours (effective playing, stoppage and resting times, number of shifts, low- and high-intensity skating activities across periods as well as passing, shooting and body checking) were analysed during the three game periods. Shift duration averaged 85.72±4.89 s (44.01±5.71 s of effective playing time and 41.71±4.07 s of stoppage) and was repeated ~7.4±1.8 times per period. Mean effective playing time and effective time per shift decreased over the periods (-6.8±17.3%, P = 0.18, d = 0.71 and -8.5±12.7%, P = 0.20, d = 0.24, respectively), resulting in a shorter distance covered (-12.8±5.7%, P = 0.16, d = 0.46) from period 1 to 3. At similar time intervals, stoppage (+8.2±9.8%, P<0.05, d = 0.78) and bench resting period (+35.6±34.0%, P<0.05, d = 1.26) also increased. The number of sprints performed in period 3 was significantly lower than in period 1 (-46.7±32.1%, P<0.01, d = 1.12). This was accompanied by a lower effective time (-16.8±24.9%, P<0.05, d = 0.82) spent in high-intensity activities (fast forward skating, forward sprinting and fast backward and sprinting) - particularly in forward sprints (-54.8±20.7%, P<0.01, d = 1.07) - in period 3 vs. 1. Detailed analysis of players' time-motion patterns of an international ice hockey game indicates that the capacity to perform intense actions is impeded towards the end of the match (period 3). Assessing performance fatigability may help practitioners to tailor ice hockey-specific training routines to help prevent in-game premature and/or excessive fatigue development.